2020
DOI: 10.3390/antibiotics9050258
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Bioactive Compounds from the Medicinal Plant Spathodea campanulata P. Beauv. and Their Activity against Helicobacter pylori

Abstract: The medicinal plant Spathodea campanulata P. Beauv. (Bignoniaceae) has been traditionally applied for the prevention and treatment of diseases of the kidney and urinary system, the skin, the gastrointestinal tract, and inflammation in general. The present work shows for the first time how chemical components from this plant inhibit Helicobacter pylori growth by urease inhibition and modulation of virulence factors. The crude extract and the main fractions of S. campanulata bark were tested on H. pylori isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…The leaf is also used to treat epilepsy (Noumi and Fozi, 2003), liver disorder (Shiracko et al, 2016), asthma (Nwauzoma and Dappa, 2013), measles (Oladunmoye et al, 2011), and sore throat (Shiracko et al, 2016). The root is used for worm infections (Musinguzi et al, 2017), stomach ache (Musinguzi et al, 2017), dysentery (Tabuti et al, 2003), and hallucination (Ior et al, 2017). The flower is used as an antidote against animal poison (Santosh et al, 2019) and cataract (Tewari et al, 2019).…”
Section: Ethnomedicinal Usementioning
confidence: 99%
See 2 more Smart Citations
“…The leaf is also used to treat epilepsy (Noumi and Fozi, 2003), liver disorder (Shiracko et al, 2016), asthma (Nwauzoma and Dappa, 2013), measles (Oladunmoye et al, 2011), and sore throat (Shiracko et al, 2016). The root is used for worm infections (Musinguzi et al, 2017), stomach ache (Musinguzi et al, 2017), dysentery (Tabuti et al, 2003), and hallucination (Ior et al, 2017). The flower is used as an antidote against animal poison (Santosh et al, 2019) and cataract (Tewari et al, 2019).…”
Section: Ethnomedicinal Usementioning
confidence: 99%
“…Specioside (8) has been detected in the flower of the plant (Elusiyan et al, 2011). Phytochemical analysis of leaves and stem bark (Ngouela et al, 1988(Ngouela et al, , 1990(Ngouela et al, , 1991 revealed the presence of different triterpenoids, viz. spathodic acid (9), 3β-acetoxyoleanolic acid (10), siaresinolic acid (11), 3β-acetoxy-12-hydroxyoleanan-28,13-olide, and oleanolic acid (16).…”
Section: Phytochemical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its ethnobotanical uses, the plant has been the subject of many phytochemical and pharmacological studies. The presence of several bioactive compounds has been reported, including flavonoids, phenolic acids, and iridoids [ 2 , 3 , 5 , 6 , 7 , 8 , 9 ]. With regard to its pharmacological properties, a wide range of biological properties, from antioxidant to antiviral, has been declared [ 2 , 3 , 5 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The work by Ngnameko et al, likewise covers the possibility offered by natural sources for the identification of bioactive molecules by reporting on the medicinal properties of Spathodea campanulata P. Beauv. (Bignoniaceae) [ 8 ]. The work shows preliminary evidence on the ability of the crude plant extract to inhibit Helicobacter pylori growth by urease inhibition and modulation of virulence factors.…”
mentioning
confidence: 99%